Higher Education Students’ Perceptions of Using Duolingo Application for English Vocabulary Improvement - Risma Putri Cahyani; Christianti Tri Hapsari (Metathesis: Journal of English Language, Literature, and Teaching, 2025)
Vocabulary mastery plays a vital role in second language learning, particularly in higher education, where students are required to comprehend academic texts, participate in discussions, and produce written work in English. Although previous studies have reported positive effects of Mobile-Assisted Language Learning (MALL) applications such as Duolingo on vocabulary development, research focusing on higher education students’ perceptions remains limited, especially in the Indonesian context. This study aimed to explore higher education students’ perceptions of using the Duolingo application to improve their English vocabulary and to identify the challenges they encounter when using it. Employing a qualitative descriptive design, data were collected through an open-ended online questionnaire administered to 25 undergraduate students enrolled in an English Education Study Program at an Indonesian university. The data were analyzed using thematic analysis following Braun and Clarke’s framework. The findings reveal that students generally perceive Duolingo positively, particularly valuing its mobility, gamification features, interactivity, instant feedback, and personalized learning experience. Students also stated that they had improved vocabulary, word recognition, and pronunciation, and considered Duolingo a helpful supplementary aid in and out of the classroom. Nonetheless, a number of shortcomings were also found, including repetition, overly simple material, limited academic vocabulary, inappropriate sentence examples, technical problems, and an inability to transfer newly learned vocabulary into real-life communication. To sum up, even though Duolingo is an effective tool for acquiring vocabulary at the novice level, its role in higher education is best situated as a learning aid rather than a standalone solution.